The Role of Soft Skills and Adversity Quotient on Work Readiness among Students in University - Jasak, Ferdy; Sugiharsono, Sugiharsono; Sukidjo, Sukidjo (Dinamika Pendidikan, 2020)
Quotient on the work readiness of students both partially and simultaneously. This research was an ex-post facto with a quantitative approach. The population of this study was 874 strata-1 students of the Faculty of Economics, Yogyakarta State University. The sample size was 275 students taken by using the proportional cluster random sampling technique. Data was collected by a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression.  The results  showed  that:  (1)  soft skills  and adversity quotient together had a positive and significant effect (p = 0,000), the simultaneous contribution of the two variables to job readiness by 33% and 67% was influenced by other variables not examined. (2) soft skills have a positive effect on work readiness (p = 0,000) with a contribution of 22%; (3) Adversity quotient has a positive effect on work readiness (p = 0,000) with a contribution of 11%. The results of this study can be followed up by  providing learning that emphasizes improving soft skills.